Overview of Key Technologies of Transmission in Massive MIMO System - Xi Yang; Shi Jin (Dianxin kexue)
With the rise of the internet of things and rapid development of the mobile internet business，higher data rate of service is demanded. Due to the ability of fully exploiting the spatial degree of freedom and obtaining good energy efficiency while improving spectral efficiency，massive MIMO has attracted wide attention worldwide. Many challenges are also brought by large antenna array at the same time of acquiring performance gain. For example，the design of transmission scheme in massive MIMO system，the dramatic increase in the complexity of hardware and the complexity of computation and so on. Firstly，some transmission strategies such as joint spatial division and multiplexing（JSDM）and massive beam-spatial division multiple access（MB-SDMA）in massive MIMO system，including their principles and transmission process were illustrated，then massive MIMO demo systems Argos and LuMaMi were presented，and the overall structure and component of the different demo systems were also provided.